9x-(5x-10)=42

Simple and best practice solution for 9x-(5x-10)=42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-(5x-10)=42 equation:


Simplifying
9x + -1(5x + -10) = 42

Reorder the terms:
9x + -1(-10 + 5x) = 42
9x + (-10 * -1 + 5x * -1) = 42
9x + (10 + -5x) = 42

Reorder the terms:
10 + 9x + -5x = 42

Combine like terms: 9x + -5x = 4x
10 + 4x = 42

Solving
10 + 4x = 42

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 4x = 42 + -10

Combine like terms: 10 + -10 = 0
0 + 4x = 42 + -10
4x = 42 + -10

Combine like terms: 42 + -10 = 32
4x = 32

Divide each side by '4'.
x = 8

Simplifying
x = 8

See similar equations:

| -14x^2-9x-10=0 | | 5x-3=-3x+35 | | 13=8-x+x | | 2x^3/3y^3/2x/y | | 23x-8=128 | | 5x+4=-14y | | y=2.7x-3.6 | | 15x=33 | | 2x+3y(x)+8=36 | | 0=-16t^2+128t+90 | | 0=-16t^2+128+90 | | -4(5n+5)+4n= | | X^2+630x-3125=0 | | 22m=6 | | 16y=20-2x | | e^6x-2e^3x-3x=0 | | y+218=6y+8 | | 5x+18=96 | | b+315=-6b+7 | | (5x+6)+(3x+23)=(9x+12) | | 180-x-(x+10)-(3x-5)=0 | | (x(X-9)(5x-18)^2)/3 | | X-5+10=25 | | 9x+36-34= | | (A^4/b^2c)^5 | | (5x+6)+(3x+23)+(9x+12)=180 | | y=10-10x | | 5x+6+3x+23+9x+12=180 | | 2x+-8y=20 | | 20-4x=7x+53 | | X=50+-4x | | x-.1x=761.20 |

Equations solver categories